Paleoclimatology : reconstructing climates of the quaternary - Bradley, Raymond S., 1948- (Elsevier, 2014)
"Paleoclimatology: Reconstructing Climates of the Quaternary, Third Edition, provides a thorough overview of the methods of paleoclimatic reconstruction and of the historical changes in climate during the past three million years. This thoroughly updated and revised edition systematically examines each type of proxy and elucidates the major attributes and the limitations of each. Paleoclimatology, Third Edition provides necessary context for those interested in understanding climate changes at present and how current trends in climate compare with changes that have occurred in the past. The text is richly illustrated and includes an extensive bibliography for further research."--